Government Innovation in Implementing the E-Pokir Application at the Pekanbaru City Regional People's Representative Council Secretariat Office: Studi Kasus di DPRD Kota Pekanbaru - Paizal, Muhammad; Febrian, Ranggi Ade (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
Indonesia is a democratic country where the people are the main holder of sovereignty in the goals of government. Public service as an orientation in providing services must support good governance to achieve this. This research was conducted with the aim of knowing and analyzing government innovation in implementing the E-Pokir application at the Pekanbaru City Regional People's Representative Council Secretariat Office. The collection techniques used were observation, interviews and documentation. The data analysis used is a descriptive qualitative method. The results of this research show that the Government's Innovation in Implementing the E-Pokir Application at the Pekanbaru City Regional People's Representative Council Secretariat Office is still not effective and implemented optimally, where in its realization there is still a lack of openness to information, especially in terms of fulfilling community aspirations. Among other things, the implementation of the e-Pokir application by the leadership and members of the Pekanbaru City DPRD is still not ideal, this application has been implemented for almost 3 years but it has not been able to be reached and observed by the community so it cannot become public data for the community as the main target of e-application innovation. Poker. The obstacles that arise in implementing this e-Pokir application innovation are that the community environment still has not received socialization, budget limitations, lack of support from related parties, and application accessibility. This application has been implemented for almost 3 years, but it has not been able to be reached and observed by the public so it cannot become public data for the community as the main target of the e-Pokir application innovation. The obstacles that arise in implementing this e-Pokir application innovation are that the community environment still has not received socialization, budget limitations, lack of support from related parties, and application accessibility. This application has been implemented for almost 3 years, but it has not been able to be reached and observed by the public so it cannot become public data for the community as the main target of the e-Pokir application innovation. The obstacles that arise in implementing this e-Pokir application innovation are that the community environment still has not received socialization, budget limitations, lack of support from related parties, and application accessibility.